MEASUREMENT OF ELECTRONIC LEARNING PERFORMANCE USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) METHOD AT THE VOCATIONAL SCHOOL OF PATRIA GADINGREJO - Eko Hendrawan; Suhendro Yusuf Irianto; Fitria Fitria (Jurnal TAM (Technology Acceptance Model), 2021)
The application of electronic learning is carried out in the learning process at Patria Gadingrejo Vocational School to determine the factors that are still weak or require improvement and the factors that are considered successful or strong in assisting the application of electronic learning in the learning process. This study results in Aydin and Tasci's ELR model questionnaire consisting of 37 statements grouped into four factors. These factors are human, self-development, technology, and innovation as well as six questions for the perception of the usefulness of electronic learning. The location of this research is at Patria Gadingrejo Vocational School. Respondents in this study were the principal, vice principal of the curriculum section, the school treasurer, the person in charge of the school computer laboratory, and teachers who are experts in e-learning. Data processing is carried out to examine the factors that influence the perceived usefulness of e-learning by using regression analysis and also the level of readiness for the application of electronic learning at Patria Gadingrejo Vocational School with Aydin and Tasci's ELR model. Aydin Tasci's electronic learning readiness (ELR) model applied to Patria Gadingrejo Vocational School gives results that are not ready for the application of electronic learning and requires a slight improvement.